Book Review: IONESCU-RUXĂNDOIU, LILIANA, MIHAELA-VIORICA CONSTANTINESCU, GABRIELA STOICA, ȘERBAN HARTULAR (EDS.), „ATTITUDE AND STANCE IN DISCOURSE”. NEWCASTLE UPON TYNE: CAMBRIDGE SCHOLARS PUBLISHING, 2022, 504 P. - COTOC, Alexandra; RADU, Anamaria (Studia Universitatis Babeș-Bolyai Philologia, 2022)
The collaborative volume Attitude and Stance in Discourse is a product of academic research, compiling papers which analyze the role stancetaking plays in oral and written discourses. The volume explores changes in meaning negotiation processes and intercultural communication and diachronic contexts. The issues are tackled from an interactional and pragma-rhetorical standpoint, but key components of the studies also comprise interdisciplinarity, cultural anthropology, and social psychology. This volume's papers are organized into six sections. The first section examines stancetaking in political and judicial discourse. A few online communicative forms represent the object of the second section. In the third section, the focus is stancetaking in conversation, as well as in fiction. In the fourth section, stancetaking is examined diachronically, taking into account its various oral and written discourses. In the fifth section, stancetaking is discussed in the framework of intercultural communication, while in the last section, the studies examine it from an applied linguistics perspective.